Analisis Pelayanan Bus Rapid Transit Kapasitas Sedang pada Sistem Transportasi Perkotaan [The Service Analysis of Medium Capacity Bus Rapid Transit on the Urban Transportation System] - Riawan, Weldy Anugra (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2018)
The improvement of the mass transportation service in urban areas such as Bus Rapid Transit recently becomes the main issue. The sustainable transportation through the development of the integrated mass public transportation including BRT acts as the main key in solving the various transportation problems in every city. The development of the urban transportation system becomes the agenda of national development. BRT managed by the government should contend against the private sector. Moreover, the government shoud focus on fixing the performance and improving public mass transportation quality. This study aims to evaluate the condition of BRT service which has been implemented in several cities in Indonesia.. The analyses used were the descriptive qualitative and SWOT. The result of this study shows that the service performance of BRT in Batam City remains poor due to the inadequate facilities to support the convenience, safety, and protection aspect for the users.Keywords: Bus Rapid Transit Medium, Urban Transportation System, Mass Transportation Service, SWOT Analysis. AbstrakPeningkatan kualitas pelayanan transportasi perkotaan terutama transportasi massal seperti Buss Rapid Transit (BRT) menjadi isu sentral pada saat ini. Pembangunan transportasi berkelanjutan melalui pengembangan angkutan umum massal yang terpadu termasuk BRT adalah kunci utama dalam menjawab permasalahan transportasi di setiap kota di Indonesia. Pembangunan transportasi massal perkotaan menjadi agenda pembangunan nasional. BRT yang dikelola oleh pemerintah harus mampu bersaing secara kompetitif dengan swasta, sehingga pemerintah harus fokus memperbaiki kinerja dan meningkatkan mutu pelayanan angkutan umum. Kajian ini bertujuan untuk melakukan evaluasi kondisi pelayanan BRT yang telah diimplementasikan pada beberapa kota di Indonesia. Analisis yang digunakan adalah analisis deskriptif kualitatif dan SWOT. Hasil dari kajian ini menunjukkan bahwa kinerja pelayanan BRT di Kota Batam masih rendah. Hal tersebut terlihat dari kondisi fasilitas yang belum memadai untuk menunjang aspek kenyamanan, keselamatan, dan keamanan pengguna jasa.